Lobectomy In Goats - John Joseph (Department of Surgery, College of Veterinary and Animal Sciences, 1989)
The present study was undertaken with the objectives of finding out a suitable anaesthetic procedure for thoracotomy, feasibility and the effects of lobectomy in goats. The study was conducted on 24 apparently healthy, male goats, aged six to nine months. They were divided into two groups of 12 animals each viz., Group I and Group II. In group I, thoracotomy alone was performed by left intercostal incision in six animals (Group IA), while thoracotomy and lobectomy were done in six animals (Group IS). In Group II, thoracotomy alone was performed by rib resection technique in six animals (Group IIA), while thoracotomy and lobectomy were done in six animals (Group IIB). Administration of chloral hydrate 6 per cent solution at the rate of I ml per 3 kg body weight, followed by thiopentone sodium 5 per cent solution, with positive pressure ventilation had given satisfactory anaesthesia for the surgical procedure. The anaesthetic affect persisted for about 30 minutes though the animals were recumbent for 4 ½ to 5 hours. During the recovery phase, incordination of movements of the head, padding of legs, rolling on the ground and frequent micturition were seen. Nasal discharge and cough were observed post – operatively. Suture materials used for thoracotomy operations were, cotton for ligation of the bronchial stump and for the ribs, silk for periosteal/intercostal and monofilament nylon for the skin incisions. Continuous sutures were inserted for the closure of the periosteum and the intercostal muscles, interrupted sutures for the adjacent ribs. Abscesses at the suture line were seen in a few animals, but wound dehiscence was not observed. There was reduction in the rectal temperature, increase in the pulse rate and no variation in the respiratory rate. There was reduction in the pH following thoracotomy, immediately after the operation, which became normal subsequently. The reduction in the haemoglobin content following thoracotomy and during post – operative period which reached near normal values by the 21st day. Serum chloride levels though varying were within the normal range. There was considerable increase in the ESR values, post – operatively, which reached near normal values by the 21st day. The increase in the plasma bicarbonate level was only marginal. The differential leucocyte count did not show any significant variation. In the present study, for anaesthesia, intravenous administration of chloral hydrate 6 per cent solution followed by thiopentone sodium 5 per cent solution to effect and maintenance of positive pressure ventilation during surgery, was found satisfactory. When lobectomy was performed by the intercostal approach five out of six animals survived and when thoracotomy alone was performed, only two animals survived. Four out of six animals in the control as well as lobectomised group survived when thoracotomy was performed by rib resettion techniques. From the results of the present study, it appears that neither the intercostal approach nor the rib resection technique for lobectomy in goats has any special advantage while considering the rate of survival. It was also found that lobectomy in goats does not interfere with the function of lungs.